In Vitro Studies of Capreomycin Sulfate Release from Polyethylcyanoacrylate Nanoparticles - Burkeev, M. Zh.; Zhaparova, L. Zh.; Tazhbaev, E. M.; Zhumagalieva, T. S.; Ali, Sayed I.; van Herk, Alex M. (Springer US, 2013)
The potential use of polyethylcyanoacrylate as a carrier for the antituberculosis agent capreomycin sulfate was demonstrated. In vitro studies addressed the release of capreomycin sulfate from polyethylcyanoacrylate nanoparticles and degradation of the polymer.
Keywords: polyethylcyanoacrylate nanoparticles; capreomycin sulfate; drug release; degradation erosion